Measuring well-being: A comparison of subjective well-being and PERMA. Issue 4 (4th July 2018) - Goodman, Fallon R.; Disabato, David J.; Kashdan, Todd B.; Kauffman, Scott Barry
Abstract: We compared Seligman's PERMA model of well-being with Diener's model of subjective well-being (SWB) to determine if the newer PERMA captured a type of well-being unique from the older SWB. Participants were 517 adults who completed self-report measures of SWB, PERMA, and VIA character strengths. Results from four analytic techniques suggest the factor underlying PERMA is capturing the same type of well-being as SWB. Confirmatory factor analysis yielded a latent correlation of r  = 0.98 between SWB and PERMA. Exploratory structural equation modeling found two highly related factors ( r  = 0.85) that did not map onto PERMA and SWB. SWB and PERMA factors showed similar relationships with 24 character strengths (average correlation difference = 0.02). Latent profile analyses yielded subgroups of people who merely scored high, low, or mid-range on well-being indicators. Our findings suggest that while lower-order indicators SWB and PERMA have unique features, they converge onto a single well-being factor.